Postoperative radiotherapy versus no postoperative radiotherapy in patients with completely resected non-small-cell lung cancer and proven mediastinal N2 involvement (Lung ART): an open-label, randomised, phase 3 trial. Issue 1 (January 2022) - Le Pechoux, Cecile; Pourel, Nicolas; Barlesi, Fabrice; Lerouge, Delphine; Antoni, Delphine; Lamezec, Bruno; Nestle, Ursula; Boisselier, Pierre; Dansin, Eric; Paumier, Amaury; Peignaux, Karine; Thillays, François; et al.
Summary: Background: In patients with non-small-cell lung cancer (NSCLC), the use of postoperative radiotherapy (PORT) has been controversial since 1998, because of one meta-analysis showing a deleterious effect on survival in patients with pN0 and pN1, but with an unclear effect in patients with pN2 NSCLC. Because many changes have occurred in the management of patients with NSCLC, the role of three-dimensional (3D) conformal PORT warrants further investigation in patients with stage IIIAN2 NSCLC. The aim of this study was to establish whether PORT should be part of their standard treatment. Methods: Lung ART is an open-label, randomised, phase 3, superiority trial comparing mediastinal PORT to no PORT in patients with NSCLC with complete resection, nodal exploration, and cytologically or histologically proven N2 involvement. Previous neoadjuvant or adjuvant chemotherapy was allowed. Patients aged 18 years or older, with an WHO performance status of 0–2, were recruited from 64 hospitals and cancer centres in five countries (France, UK, Germany, Switzerland, and Belgium). Patients were randomly assigned (1:1) to either the PORT or no PORT (control) groups via a web randomisation system, and minimisation factors were the institution, administration of chemotherapy, number of mediastinal lymph node stations involved, histology, and use of pre-treatment PET scan. Patients received PORT at a dose of 54 Gy in 27 or 30 daily fractions, on five consecutive days a week. Three dimensional conformal radiotherapy was mandatory, and intensity-modulated radiotherapy was permitted in centres with expertise. The primary endpoint was disease-free survival, analysed by intention to treat at 3 years; patients from the PORT group who did not receive radiotherapy and patients from the control group with no follow-up were excluded from the safety analyses. This trial is now closed. This trial is registered with ClinicalTrials.gov number, NCT00410683 . Findings: Between Aug 7, 2007, and July 17, 2018, 501 patients, predominantly staged with 18 F-fluorodeoxyglucose ( 18 F-FDG) PET (456 [91%]; 232 (92%) in the PORT group and 224 (90%) in the control group), were enrolled and randomly assigned to receive PORT (252 patients) or no PORT (249 patients). At the cutoff date of May 31, 2019, median follow-up was 4·8 years (IQR 2·9–7·0). 3-year disease-free survival was 47% (95% CI 40–54) with PORT versus 44% (37–51) without PORT, and the median disease-free survival was 30·5 months (95% CI 24–49) in the PORT group and 22·8 months (17–37) in the control group (hazard ratio 0·86; 95% CI 0·68–1·08; p=0·18). The most common grade 3–4 adverse events were pneumonitis (13 [5%] of 241 patients in the PORT group vs one [<1%] of 246 in the control group), lymphopenia (nine [4%] vs 0), and fatigue (six [3%] vs one [<1%]). Late-grade 3–4 cardiopulmonary toxicity was reported in 26 patients (11%) in the PORT group versus 12 (5%) in the control group. Two patients died from pneumonitis, partly related to radiotherapy and infection, and one patient died due to chemotherapy toxicity (sepsis) that was deemed to be treatment-related, all of whom were in the PORT group. Interpretation: Lung ART evaluated 3D conformal PORT after complete resection in patients who predominantly had been staged using ( 18 F-FDG PET-CT and received neoadjuvant or adjuvant chemotherapy. 3-year disease-free survival was higher than expected in both groups, but PORT was not associated with an increased disease-free survival compared with no PORT. Conformal PORT cannot be recommended as the standard of care in patients with stage IIIAN2 NSCLC. Funding: French National Cancer Institute, Programme Hospitalier de Recherche Clinique from the French Health Ministry, Gustave Roussy, Cancer Research UK, Swiss State Secretary for Education, Research, and Innovation, Swiss Cancer Research Foundation, Swiss Cancer League.